Aplicação de fibra de carbono como material radiotransparente em instrumental cirúrgico - Pinto, Ana Claudia Gaicoski (2015)
This paper aims to describe the investigation of a radiolucent material, for applying in surgical instruments, especially in orthopedic surgeries. The research proposes a redesign of the product, to develop the manufacturing process and conduct clinical and mechanics tests. It was applied the methodology for the selection of materials proposed by Asbhy (2012) to analyze the possible materials with the needed requirements to the project, such as a lower density than the steel, sterilization capability and the radiolucency. The material that presented the required characteristics was the carbon fiber. From the material selection, we began the process of manufacturing, to which was adopted the vacuum forming. After the performing of the clinical and mechanical tests, it was observed that the Hohmann retractor met the stated objective of the radiolucency, and that also the product shall be sterilized, without modifying its mechanical characteristics to the tested cycles.